Development and validation of a self-assessment scale of job performance in teleworking - García-Salirrosas, Elizabeth Emperatriz (2022)
The study proposes an instrument to evaluate the work performance of teleworkers (JOPERTE), identifying 19 items, which makes it an easy-to-apply instrument for the evaluation of work performance. The pilot test consisted of 312 participants who stated that they were working in the telecommuting modality. The items were formulated after having carried out an exhaustive review of the literature to later be evaluated by experts who guaranteed the content of the construct. Exploratory and confirmatory factor analyzes were applied to evaluate the proposed model, the results revealed a one-dimensional scale with a good fit of the model that met all the CMIN, DF, CMIN/DF, CFI, SRMR, RMSEA and PClose indicators satisfactorily. In this way, this scale allows the authors to provide the scientific and business community with a reliable instrument to be applied both in future research and to evaluate workers in organizations where they work in virtual environments.